Kemanusiaan Vs Kapitalisme di Era Pandemi Corona Virus Disease-19 (COVID19): Ekslusifitas Paten Vs Lisensi Wajib - Fatizah, Sheylla (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Corona Virus Disease-19 (COVID-19) began to spread to various parts of the world since December 2019, which was first discovered in Wuhan, China. Of course this has brought great disaster to 216 countries in the world, because no country is immune to this virus and the epidemic has spread to various continents and attacked many aspects of the world community. Distressing conditions like this require the state to play a stronger role by providing better service protection. In addition, conditions like this raise big questions about how countries in the world deal with this. In the midst of the COcVID-19 pandemic, many scientists are racing to quickly find an effective vaccine to fight this virus. An example of one that succeeded is the discovery of Sinovac or called CoronaVac, where this vaccine is the result of research from Sinovac Biotech Co. which is a biopharmaceutical company focused on research, development, manufacture and commercialization of vaccines, and the company is based in Beijing, China. Seeing the COVID-19 pandemic that is increasingly paying attention, especially in developing countries, many countries are pressing for the temporary waiver of COVID-19 vaccine patents during this crisis. The reason is none other than so that production can be accelerated so that it is expected to be able to handle the COVID-19 pandemic. Of course this raises a polemic between developed countries and developing countries where there are two different interests, one country protects its investors and the other one protects its people. From this we can see that COVID-19 leaves a lot of room for its own problems.